Engineering properties of five varieties of coconuts (Cocos nucifera L.) for efficient husk separation. Issue 4 (2nd April 2020) - Pandiselvam, R.; Manikantan, M.R.; Kothakota, Anjineyulu; Rajesh, G.K.; Beegum, Shameena; Ramesh, S.V.; Niral, V.; Hebbar, K.B.
ABSTRACT: Coconut husk is used as a natural fiber, and it is constantly gaining economic importance including in organic farming. Yet, there are major knowledge gaps regarding the engineering properties of coconut to design efficient coconut dehusking and coir manufacturing process. A sample of 40 coconuts of each variety, namely Malayan Yellow Dwarf, Malayan Orange Dwarf, Kera Shankara, Chowghat Orange Dwarf, and Chowghat Green Dwarf, were divided into two groups (20 dry and 20 green coconuts), and different engineering properties were measured. It was observed that coconuts show an extensive diversity in size, density, husk thickness, husk weight, shell thickness, shell weight, and kernel thickness, depending on variety and maturity. The present investigation provides necessary information and the need for classifying the coconut fruits based on size/variety rather than weight to design superior coconut dehusking machine.